Visuospatial working memory capacity moderates the relationship between anxiety and OCD related checking behaviors - Wang, Pengchong; Yan, Zijun; Chen, Tao; Cao, Wenwen; Yang, Xiangyun; Meng, Fanqiang; Liu, Yuqing; Li, Zhanjiang (Frontiers in Psychiatry, 2023)
Background: Compulsive checking behavior is the most prevalent compulsive behavior in patients with obsessive-compulsive disorder (OCD). While some studies have shown that anxiety and executive function influence compulsive checking behavior, the relationship between these constructs is inconclusive. Hence, we sought to explore the interplay between executive function, anxiety and compulsive checking behavior. Method: 47 healthy participants (HC) and 51 patients with OCD participated in the study. Symptoms and emotional states were assessed using the Yale-Brown Obsessive Compulsive Scale, the Obsessive-Compulsive Inventory-Revised, the Beck Anxiety Inventory, and the Beck Depression Inventory. Participants also completed three tests of neuropsychological functioning: the Stop Signal Task, the Spatial working memory Task, and the Wisconsin card sorting test. We analyzed the relationships between anxiety, executive function, and compulsive checking symptoms. Results: Patients with OCD showed significantly greater anxiety (p<0.001) and impairments in visuospatial working memory function (p=0.030) compared to HC participants, while inhibition and set-shifting were not significantly different between the two groups. Visuospatial working memory was negatively related to compulsive checking behavior (p=0.016). Visuospatial working memory also played a moderating role in the positive relationship between anxiety and compulsive checking behavior (β=-0.281, p=0.022). Conclusion: Anxiety symptoms play an important role in explaining compulsive checking behavior in patients with OCD who have relatively weak visuospatial working memory ability. These findings provide a foundation for further research regarding the roles of emotion and cognitive inflexibility in compulsive checking behavior in patients with OCD.